Love, health, and robots: Automation, migration, and family responses in rural China - Ruini Zhu; Ye Yuan; Yaojing Wang (China Economic Review, 2024)
As industrial automation supplants labor, there are important consequences on the labor market, especially for the vast rural population in developing countries. This study investigates how industrial automation, particularly the use of robots, affects the employment and mobility of young rural workers and the decision-making of their elderly parents in China. Using longitudinal data from rural Chinese households and a shift-share approach, we find automation in urban areas decelerates the rural-to-urban migration. This slowdown is accompanied by a reduction in rural workers' employment opportunities and an increase in their propensity to co-reside with their elderly parents in their home counties, which in turn alters their parents' financial decisions, including labor supply, savings, and family transfers. Notably, rural workers' decision to stay and co-reside with their senior parents fosters more frequent family interactions, contributing to notable improvements in the elders' mental and physical health. Our study underscores the complex effects of automation on labor mobility, family relationships, and the overall well-being of the rural populace in the face of technological advancements.